2019
DOI: 10.1332/239788219x15622468259858
|View full text |Cite
|
Sign up to set email alerts
|

“Time is more important than anything else”: tensions of time in the home care of older adults in Ireland

Abstract: This article explores perceptions of time reported by service users, family carers, care workers, nurses, social workers and agency managers across home support services for older adults in Ireland. The findings are organised around: time spent waiting for care; time spent ‘processing’ care across primary and secondary care boundaries; time and person-centred care; and time, technology and communication. Time emerges as a problematic aspect of all processes and structures around formal home care, suggesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 17 publications
2
23
0
Order By: Relevance
“…Some chose home care work after having worked in institutional settings, preferring the one-on-one, the reduced stress of not having to rush, and the autonomy to create their own schedules and manage their own workflow, all aspects related to having time. The importance of having time to provide care reflects the recent findings of McDonald, Lolich, and Warters (2019), who found that time was essential to providing quality person-centered care. In our study, those who experienced disempowering aspects of the job identified mostly structural aspects of empowerment, including access to support, resources, information and opportunity.…”
Section: Discussionmentioning
confidence: 80%
“…Some chose home care work after having worked in institutional settings, preferring the one-on-one, the reduced stress of not having to rush, and the autonomy to create their own schedules and manage their own workflow, all aspects related to having time. The importance of having time to provide care reflects the recent findings of McDonald, Lolich, and Warters (2019), who found that time was essential to providing quality person-centered care. In our study, those who experienced disempowering aspects of the job identified mostly structural aspects of empowerment, including access to support, resources, information and opportunity.…”
Section: Discussionmentioning
confidence: 80%
“…It would be useful to note findings from research such as that from the European Foundation for the Improvement of Living and Working Conditions (2020) 4 which has shown that working from home does not always result in decreased working times, and for remote working to be sustainable, challenges such as overtime working need to be addressed, an issue that is especially pertinent for those combining work and caring. Time is really important to family carers, and in addition to considering how to make extra time available to family carers through workplace measures, it could be worth considering how certain issues around time could potentially be addressed through the reconfiguration of health and social care services (McDonald et al, 2019) 5 . Time taken up in this sphere has knock-on effects for working time.…”
Section: Open Peer Reviewmentioning
confidence: 99%
“…With this participant, multiple professional services in addition to daily personal support were involved, resulting in more than one visit on some days. HC visits have previously been reported as intrusive and disruptive to one’s normal routine, and described as an invasion of space and time [ 45 ]. Shared-decision making is preferred by clients and may have mitigated this burden pre-emptively [ 46 ].…”
Section: Discussionmentioning
confidence: 99%